A novel technique for stabilisation of a proximal cervical vertebral fracture in a tawny eagle (Aquila rapax). Issue 1 (16th December 2013) - Dutton, Thomas Anthony George; Calvo Carrasco, Daniel; Sabater, Mikel; Forbes, Neil
Abstract : A proximal cervical vertebral fracture was stabilised using a novel technique involving a trans‐sinus pin and neck brace formed from ventilated white thermoplastic mesh bandage. This simple technique provided safe and effective coaptation reducing the risk of vertebral destabilisation and spinal cord injury. The brace and pin were kept in place for four weeks. During this time food was provided to the eagle via an ingluviotomy tube allowing provision of a balanced liquid critical‐care formula in a stress‐free manner. After implant removal, the eagle made a full recovery with no reported loss of neck mobility or neurological derangements.